(untitled) (The Review of Diabetic Studies, 2025)
In low- and middle-income nations, medication errors result in 134 million adverse events per year, costing 42 billion worldwide and causing 400,000 avoidable deaths in the United States. In order to improve drug safety and health security, this systematic scoping review looks at integrated approaches combining nurses, pharmacists, and laboratory specialists. PubMed, Scopus, and Web of Science were searched (2019–2025) for studies on triadic cooperation in accordance with PRISMA-ScR standards; 52 publications from 1,247 hits were found. Labs offer therapeutic drug monitoring (TDM) and biomarkers, which reduce toxicity by 25–30%; pharmacists optimize dosage and identify interactions (60 percent of discrepancies are found); and nurses guarantee administration adherence. Key findings: interdisciplinary teams enhanced adherence by 22–26%, decreased mistakes by 28% (95% CI: 22–34%), and decreased hospitalizations by 15–33%. Studies from Saudi Arabia and Egypt show that polypharmacy poses a risk to chronic care, and that interprofessional education (IPE) can help close TDM gaps. Communication silos (40% gaps) and hierarchies are obstacles that are lessened via joint rounds and electronic health records (EHRs). Consequences for environments with limited resources, such as Cairo: requiring triads might reduce errors by half, saving 1,200 each patient. Future studies require Using AI and RCTs in pediatrics and rural health. In this appraisal, policy-driven triads are encouraged in the case of WHO Medication Without Harm.."